2002年夏季南极普里兹湾及其邻近海域浮游植物现存量、初级生产力粒级结构和新生产力研究 - 刘诚刚; 宁修仁; 孙军; 蔡昱明; 曹建平 (2004)
2002年1～2月,在南极普里兹湾及其北部海区对浮游植物生物量、优势种类组成、细胞丰度、初级生产力和新生产力的观测结果表明,叶绿素a浓度、初级生产力和新生产力的高值均出现在湾内及湾口陆架区,并且远高于陆坡和深海区.湾内和湾口陆架区表层叶绿素a浓度均高于1mg/m3,平均为(2 34±0 85)mg/m3,而陆坡区和深海区平均只有(0 19±0 14)和(0 15±0 05)mg/m3.湾内和陆架区平均初级生产力[(355 8±192 1)mg/(m2·d)]高于陆坡区[(82 0±20 8)mg/(m2·d)]和深海区[(100 5±83 4)mg/(m2·d)].在陆坡和深海区初级生产力的粒级结构以微微型浮游生物(<2μm)对初级生产力的贡献最大(分别为49 6%和46 2%),湾内和陆架区则以小型浮游生物(为20～280μm)的贡献为主(66 2%).在湾内和湾口陆架区同时具有较高的新生产力和再生生产力. The composition of dominant species, the cell abundance, size fractionated biomass and productivity, and the new prodution of phytoplankton are studied in the Prydz Bay and its adjacent sea area during the 18th CHINARE cruise. The results show that there is marked feature of spatial zonation in the sea areas investigated. In the Prydz Bay and its adjacent continental shelf, the standing stock, and produtivity and new production are much higher than those of continental slope and deep-sea area. The results of size-frationed producitvity show that the contribution of net plankton to the total productivity (49.6% and 46.2% respectively) is the largest in the continental slope and deep-sea area, and the productivity of picoplankton is the dominant composition of total productivity (66.2%) in the bay and continental shelf area. 国家自然科学基金资助项目(49876032).